Barriers and Breakthroughs in Targeting the Oxytocin System to Treat Alcohol Use Disorder - Ryabinin, Andrey E.; Zhang, Yangmiao (Frontiers in Psychiatry, 2022)
Development of better treatments for alcohol use disorder (AUD) is urgently needed. One promising opportunity for this development is the potential of targeting the oxytocin peptide system. Preclinical studies showed that administration of exogenous oxytocin or, more recently, stimulation of neurons expressing endogenous oxytocin lead to a decreased alcohol consumption across several rodent models. Initial clinical studies also showed that administration of oxytocin decreased craving for alcohol and heavy alcohol drinking. However, several more recent clinical studies were not able to replicate these effects. Thus, although targeting the oxytocin system holds promise for the treatment of AUD, more nuanced approaches toward development and application of these treatments are needed. In this mini-review we discuss potential caveats resulting in differential success of attempts to use oxytocin for modulating alcohol use disorder-related behaviors in clinical studies and evaluate three directions in which targeting the oxytocin system could be improved: (1) increasing potency of exogenously administered oxytocin, (2) developing oxytocin receptor agonists, and (3) stimulating components of the endogenous oxytocin system. Both advances and potential pitfalls of these directions are discussed.